Photoisomerization of azobenzene-substituted alkanethiolates on Au(111) substrates in the context of work function variation: the effect of structure and packing density. Issue 18 (24th April 2019) - Schuster, Swen; Füser, Matthias; Asyuda, Andika; Cyganik, Piotr; Terfort, Andreas; Zharnikov, Michael
Abstract : Novel azobenzene-substituted self-assembled monolayers were used for stimuli-responsive work function variation, with control of the molecular dipole and sterical constraints. Abstract : Photoisomerization of a series of custom-designed, azobenzene-substituted alkanethiolate (AT) self-assembled monolayers (SAMs) on Au(111) substrates was studied in the context of work function variation, using Kelvin probe measurements as a transduction technique. These SAMs featured variable packing density (by ∼14%; due to the odd–even effects) and, as an option, were additionally decorated with the electron donating/withdrawing –CH3 and –CF3 tail group, respectively, which induce additional dipole moments. The efficiency of photoisomerization and the respective extent of work function variation (Δ Φ ) were found to be quite low and independent of the packing density in the SAMs, within the given odd–even packing density variation. They could only be increased, up to ca. 40 meV for Δ Φ, by mixing the azobenzene-substituted ATs with shorter "matrix" molecules, which were introduced for a partial release of the sterical constraints. The Δ Φ values for the SAMs decorated with the –CH3 and –CF3 tail groups were found to be lower than those for the monolayers without such a decoration, which correlated well with the theoretical estimates for the change of the dipole moment of the relevant molecules upon the photoisomerization.